Satisfação dos clientes: um estudo realizado com a Empresa Eletrocar - Orth, Pedro Roberto (2023)
The objective of this study is to measure the degree of customer satisfaction of the company Eletrocar, a public company in the city of Carazinho-RS. As for the methodological procedures, the research took place in two stages, the first being qualitative, with 9 interviewees, and the second stage, which took place through the online tool Google Forms, being quantitative, with 90 respondents. The data obtained were tabulated and analyzed to measure the degree of customer satisfaction in relation to the service offered, service provided, payments and deadlines, energy distribution and electrical network. With this, it was possible to identify which indicators the company has the highest satisfaction, being the stability in the electrical network, the payment options and the face-to-face service, where the company must strive to maintain these levels. Also identify where there are the biggest causes of dissatisfaction for customers, being the number of wires on the poles, flag change and the price practiced. Given this, it is evident where the company can focus to increase the satisfaction of its customers